Answer:
Explanation:
The inverse function gives back the input of the original function when we put in the original output.
In other words, if the original function does the following.
f(input) = output
Then the inverse function does the following.
f^-1(output) = input
Now in our case, we have f(3) = 7; therefore, the inverse function should give
![\boxed{f^(-1)\left(7\right)=3.}](https://img.qammunity.org/2023/formulas/mathematics/college/mimf2mhi7oopba5tqt6hez4emxx4qpupl1.png)
If we have f( -5) = - 10, then the inverse function should give
![\boxed{f^(-1)(-10)=-5.}](https://img.qammunity.org/2023/formulas/mathematics/college/xv8z48h8t1k6sgmxx2fvre4awmbrfftc7a.png)
Hence, choices 1 and 5 are the correct answers!